Observations on evaluation of vertical tapping as a crop harvesting method of rubber (Hevea brasiliensis)- Performance of clone RRII 105 to vertical tapping under d3 6d/7 frequency of tapping - Rajagopal R; Karunaichamy K (PLACROSYM XXIII. Climate Resilient Technologies for Sustainability of Plantation Crops, 6-8 March 2019, Central Coffee Research Institute, Chikkamangaluru, Karnataka, India, Abstracts, p.74.)
Natural rubber (NR) is obtained commercially from Hevea brasiliensis by the process of controlled wounding called tapping. Rubber plantation industry in India is facing crisis for the last few years due to fluctuating lower rubber price, shortage of skilled tappers, climatic constraints and many other allied factors. After evaluation of different tapping systems, the present day tapping system of half spiral downward cut was evolved. Optimising tapping systems with appropriate dose and frequency of ethephon applicaiton can be one of the approaches to address shortage of skilled tappers and can help in realising potential yield from rubber trees. In the present scenario, yield stimulation technology has been perfected and advocated to get promising yield under lower frequencies of tapping, from mini cuts or from punctures with gaseous/ethephon stimulation. Research data on response of mature rubber trees to vertical tapping with stimulation either on virgin or on renewed panels is meagre. Hence, a Randomized Block Design experiment with five treatments and five replications comprising of S/2 d3 6d7 (standard practice) and vertical tapping cuts of 22 and 10 cm cut lengths with different levels of yield stimulation with 2.5;ethephon was conducted for four years to examine the scope and feasibility of vertical tapping as latex harvest technology tool for crop extraction of mature rubber trees of clone RRII 105. Initial results from the study indicated promise of adoption of vertical tapping of 22 cm (with ET 2.5;12 or 24 rounds per year) or 10 cm (with ET 2.5;24 or 36 rounds year) with yield level at par with standard recommended crop harvesting practice (S/2 d3 6d7 ET 2.5;3 rounds per year) without deleterious effect. The system is also having the additional advantage of tapping one panel for two years unlike in half spiral downward tapping panel marked for one year which can be tapped only for a year.
Keywords: RRII 105; Rubber; Vertical tapping; Yield